The wounded researcher : research with soul in mind - Romanyshyn, Robert D. (Robert Donald), 1942- (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"The Wounded Researcher addresses the crises of epistemological violence when we fail to consider that a researcher is addressed by and drawn into a work through his or her complexes. Using a Jungian-Archetypal perspective, this book argues that the bodies of knowledge we create degenerate into ideologies, which are the death of critical thinking, if the complexity of the research process is ignored. Writing with soul in mind invites us to consider how we might write down the soul in writing up our research"--
"First published in 2013 by Spring Journal Books"--Verso.
OCLC-licensed vendor bibliographic record.
Keywords: Psychology -- Philosophy; Psychology -- Research; Phenomenological psychology; Soul; PSYCHOLOGY / Mental Health; PSYCHOLOGY / Movements / Jungian